2020
DOI: 10.1002/bjs.11507
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and outcomes of chronic opioid use following trauma

Abstract: Background The growing problem of opioid misuse has become a serious crisis in many countries. The role of trauma as a gateway to opioid use is currently not determined. The study was undertaken to assess whether traumatic injury might be associated with chronic opioid use and accompanying increased long‐term mortality. Methods Injured patients and controls from Sweden were matched for age, sex and municipality. After linkage to Swedish health registers, opioid consumption was assessed before and after trauma.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 40 publications
2
46
1
1
Order By: Relevance
“…33À37 Although OUD trauma patients appear to have lower long-term survival related to substance abuse, the underlying mechanisms of lower in-hospital mortality warrant further investigation. 38,39 Nevertheless, OUD appears to result in significant morbidity and negatively impact resource use. A prior study by Cannon et al demonstrated OUD trauma patients have longer intensive care duration of stay and need for mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…33À37 Although OUD trauma patients appear to have lower long-term survival related to substance abuse, the underlying mechanisms of lower in-hospital mortality warrant further investigation. 38,39 Nevertheless, OUD appears to result in significant morbidity and negatively impact resource use. A prior study by Cannon et al demonstrated OUD trauma patients have longer intensive care duration of stay and need for mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…Vi vet ikke hva slags muntlig informasjon pasientene fikk, men dette er i lys av den aktuelle diskusjonen om opioidmisbruk et viktig forbedringspunkt. Det er vist i et svensk materiale at risikoen for opioidmisbruk var mer enn tre ganger så stor hos dem som hadde vaert utsatt for skade enn hos kontrollpopulasjonen (5). Spesielt langvarig bruk etter utskrivning etter en skade eller operasjon er assosiert med økt fare for misbruk (6).…”
Section: Resultaterunclassified
“…While some researchers have found that opioids prescribed after acute traumatic injury do not lead to long-term use, others have found that a significant number of patients prescribed chronic opioids misuse opioid analgesics, and there is an independent association with increased risk of death in the 6-18 months following trauma in those patients with chronic opioid use. 23,26,27 Thus, pain management algorithms that adequately treat severe pain while simultaneously lowering opioid use should be pursued. 28 We also evaluated clinically significant secondary endpoints, including pulmonary complications and length of hospital stay.…”
Section: Discussionmentioning
confidence: 99%